Master the art of Cell Culture! Workshop 2024 / Nur Fathiah Mohd Radzi - Mohd Radzi, Nur Fathiah (Faculty of Pharmacy, 2024)
From May 28 to May 30, 2024, the "Master the Art of Cell Culture! Workshop 2024" was successfully conducted. This workshop was organized by the Tissue Culture Unit of the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) in collaboration with Biomarketing Services (M) Sdn Bhd. The workshop featured a select group of ten participants, comprising students from Universiti Sultan Zainal Abidin (UniSZA), Terengganu, and Universiti Malaysia Sarawak (UNIMAS), Sarawak, alongside staff and students from various UiTM faculties and a centre of excellence, namely the Faculty of Pharmacy, Medicine, Dentistry, and the Atta-ur-Rahman Institute for Natural Products Discovery (AuRIns) centre.